Gooino - Kamaruddin, Siti Faridah; Abang Abdul Rahman, Dayang Hummida; Juhari, Nur Nadia Qausar; Pengiran Mahtar, Pengiran Saifudzin; Bujang, Azlina (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Gooino is a digital marketing mobile application (DMMA) that helps consumers to discover high-quality, locally produced goods and supports small town entrepreneurs such as in Tellian, Mukah to market their goods digitally. Gooino aims to tackle many issues such as poor monthly income among Tellian entrepreneurs, difficulty in selling Mukah products across Sarawak and Malaysia, lack of exposure to Mukah's famous sago-based products with its advantages and nutrients, and and communication barriers between non-Melanau Mukah speakers and Mukah people. The development of Gooino aims to assist Tellian entrepreneurs to earn extra income, promote local products widely not only in Sarawak, educate the public about the advantages and nutrients of sago-based products, and help the non-Melanau Mukah speakers to communicate with Tellian entrepreneurs. Gooino has a user-friendly interface that targets entrepreneurs as well as potential customers with features that allow entrepreneurs to register their businesses and update the information about their products while customers can communicate with the entrepreneurs directly for any inquiries. Three factors make Gooino a unique smartphone app: (1) Sarawak's first mobile app that promotes Mukah's distinctive tourist destinations and local items, (2) In partnership with CRAUN Research, this application will provide nutritional information for all Mukah entrepreneurs' products, notably those from Kampung Tellian, (3) This mobile app promotes the uniqueness of the Mukah Melanau Language, enabling customers to connect with local entrepreneurs and tourists who wish to visit Mukah but are worried about language barriers. Gooino will be released for free on the iOS and Android platforms. TVS, a Sarawak broadcaster, will also promote this application. This application registered its copyright (LY2021Q02670) and trademark (PSA20211058).